2013
DOI: 10.1021/jp312202j
|View full text |Cite
|
Sign up to set email alerts
|

Glycolaldehyde Monomer and Oligomer Equilibria in Aqueous Solution: Comparing Computational Chemistry and NMR Data

Abstract: A computational protocol utilizing density functional theory calculations, including Poisson-Boltzmann implicit solvent and free energy corrections, is applied to study the thermodynamic and kinetic energy landscape of glycolaldehyde in solution. Comparison is made to NMR measurements of dissolved glycolaldehyde, where the initial dimeric ring structure interconverts among several species before reaching equilibrium where the hydrated monomer is dominant. There is good agreement between computation and experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
130
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(146 citation statements)
references
References 60 publications
16
130
0
Order By: Relevance
“…Implicit assumptions in their analysis were that the GA solution was all monomer (GA and GA hydrate) and that aqueous hydration-dehydration kinetics were "fast" compared to the gas-aqueous equilibration timescale of their experimental system. However, Kua et al (2013) reported that a 1 M GA monomer equivalent aqueous solution is a mixture of monomers and several dimer and trimer compounds. GA monomers were found to comprise approximately 55 % of their solution with the monomer making up 3 % and the monomer hydrate 52 %.…”
Section: Reagent Gasmentioning
confidence: 99%
See 1 more Smart Citation
“…Implicit assumptions in their analysis were that the GA solution was all monomer (GA and GA hydrate) and that aqueous hydration-dehydration kinetics were "fast" compared to the gas-aqueous equilibration timescale of their experimental system. However, Kua et al (2013) reported that a 1 M GA monomer equivalent aqueous solution is a mixture of monomers and several dimer and trimer compounds. GA monomers were found to comprise approximately 55 % of their solution with the monomer making up 3 % and the monomer hydrate 52 %.…”
Section: Reagent Gasmentioning
confidence: 99%
“…GA monomers were found to comprise approximately 55 % of their solution with the monomer making up 3 % and the monomer hydrate 52 %. Using the experimental equilibrium constants determined from Kua et al (2013) and our "as monomer" aqueous concentration, our aqueous solution was expected to be 91 % monomer hydrate, 6 % monomer with the remaining 3 % nearly all dimer. Kua et al also indicated the kinetics of the trimer and dimer equilibration was "slow," up to a few hours.…”
Section: Reagent Gasmentioning
confidence: 99%
“…Glycolaldehyde in solution is known to exist in several different forms. The dimeric glycolaldehyde ring is interconverting between several different forms before reaching equilibrium where the hydrate (geminal diol) form of the substrate is dominant (44). Since only freshly solubilized glycolaldehyde dimer was accepted as a substrate, we assume that the dimeric structure, containing two hydroxyl groups, is the form that is oxidized by the enzyme.…”
Section: Characterization Of a Novel Raffinose Oxidasementioning
confidence: 99%
“…The dimer then may form a five member ring species. Thus, it is believed that nine to thirteen different molecular species are present in a water solution of DHDO, some of which are shown in Figure 5 (11,12). The equilibrium of species in organic solvents and in the molten state was studied by Yaylayan and coworkers, who showed partial ring opening of DHDO and cyclization into the five-member cyclic compound 2-hydroxymethyl-4-hydroxyl,1,3-dioxolane (13).…”
Section: The Monomer: Glycolaldehydementioning
confidence: 99%
“…The spectrum contains a small signal at 5.52 ppm that we tentatively assign to terminal CHOH. Small signals due to side products are also present such as the small, sharp peaks at 5.63 and 4.73 ppm because of a small amount of five-membered ring present due to rearrangement (12), the peak at 6.70 ppm which is due to protons on a carbon-carbon double bond, and the peaks at 9.54 ppm which are due to aldehyde protons. Aldehyde may form if the terminal unit of the polymer ring opens, as shown in Figure 17, top.…”
Section: Figure 15 1 H Nmr Specrum Of Pdhdo Prepared Using Sc(otf) 3mentioning
confidence: 99%